Proposal for the development of a manual for the management of student conflicts - Chacón Mora, Armando (2013)
This article is a modern proposal for the management of student conflicts, based on the research of qualitative type whose title was “Analysis of the perception of the student conflicts in public schools in Costa Rica”. Today there are many manifestations of conflicts that occur daily in the national educational organizations, and on which many teachers and principals feel impotence not by lack of  capacity but by lack of tools for the prevention and efficient attention for this type of situation. From this perspective, it is essential to promote social skills in students preparing a manual of mediation which not only serves as a means of information, and training, but it constitutes a tool for mediation for the management of student conflicts of public institutions in Costa Rica. This manual shall consist of activities aimed to encourage values, principles and attitudes needed to collaborate with the student conflict management. These social skills are related to aspects such as: promotion of critical thinking; assertive communication, the promotion of resilience; the values that collaborate with the coexistence and the culture of peace, among others.